PROMOTING EDUTOURISM AND SUSTAINABLE WASTE MANAGEMENT IN SANTEN ISLAND BEACH, INDONESIA, THROUGH COMMUNITY EMPOWERMENT - Sari, Jayanti Dian Eka; Yulianti, Yunika Tri; Firmansyah, Januar; Fikri, Faisal; Yudhana, Aditya; Praja, Ratih Novita; Mandagi, Ayik Mirayanti; Hairi, Farizah Mohd (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2024)
Santen Island Beach in the Banyuwangi Regency of Indonesia possesses immense potential for beach tourism. Unfortunately, the charm of this destination has been marred by inadequate waste management. This paper outlines a community service program aimed at enhancing awareness, understanding, and active participation of local community groups in addressing waste management issues by transforming waste into ecobrick greenhouses. The program employed various methods, including lectures, discussions, and brainstorming sessions, which were conducted on Pulau Santen Beach with a focus on the local population. The application of a local development model was central to our community service activities, resulting in increased understanding, awareness, and participation among the target groups. The heightened involvement was marked by enthusiastic participation in ecobrick production, effective household waste sorting (particularly plastic waste), and the formation of committed cadres. The local community exhibited increased knowledge through their ability to respond to questions and plan follow-up actions. This initiative significantly improved the knowledge, awareness, and engagement of the target community in managing waste and converting it into ecobricks.